Impaired coronary flow reserve immediately after coronary angioplasty in patients with acute myocardial infarction. Issue 4 (April 1993) - Ishihara, M; Sato, H; Tateishi, H; Kawagoe, T; Yoshimura, M; Muraoka, Y
Abstract : OBJECTIVE–To examine coronary flow reserve immediately after emergency coronary angioplasty in patients with acute myocardial infarction. DESIGN–A 3 F coronary Doppler catheter was used to measure coronary blood flow velocity in the infarct artery and in the non-infarct artery. Maximal hyperaemia was produced by 10 mg of intracoronary papaverine and coronary flow reserve was calculated. PATIENTS–11 patients with acute myocardial infarction undergoing both emergency coronary angioplasty (4.7 (3.6) h after the onset of chest pain (mean (SD))) and at follow up catheterisation 16 (4) days after angioplasty. SETTING–Hiroshima City Hospital. RESULTS–There was no stenosis of > or = 50% in the coronary artery of interest. Immediately after coronary angioplasty the mean (1 SD) coronary flow reserve of the infarct artery was significantly less than that of the non-infarct artery (1.4 (0.4) v 2.8 (0.8), p < 0.001). At follow up catheterisation the coronary flow reserve of the infarct artery increased almost to the value of the non-infarct artery (2.8 (1.2) v 3.1 (0.8) p = NS). CONCLUSION–The coronary flow reserve in the infarct region was severely impaired immediately after reperfusion, even with a widely patent infarct artery. This could restrict the beneficial effects of reperfusion therapy, especially when there is a severe residual stenosis.